(untitled) (Malaysian Journal of Learning and Instruction, 2025)
Purpose - Previous studies have generally focused on TESOL teachers in English as a Foreign Language (EFL) classes, this study however, investigates English Medium of Instruction (EMI) in non-English language teaching contexts. This study fills a gap in the current literature on EMI by analyzing the problems and practices of 46 Thai university lecturers who use English as the medium of instruction in various subject fields. Method - Utilizing an explanatory mixed-method study design, data was gathered through a survey questionnaire and interviews. This methodology facilitated the acquisition of a thorough comprehension of the perspectives and obstacles encountered by Thai lecturers using EMI in content courses. Findings - The results of the study indicate that Thai lecturers generally hold different attitudes towards the use of EMI. Their apprehension stems from the degree of readiness of the students, including a perceived deficiency in skills and linguistic proficiencies, and the extent of help provided by the institution. Despite the challenges, Thai lecturers demonstrated flexibility by employing several pedagogical approaches within the classroom setting to accommodate the distinct requirements of their subject matter. Significance - The study’s relevance resides in its implications for policy formulation, curriculum design, and teacher professional development initiatives. The results of this study have highlighted the significance of providing customized assistance to lecturers and the necessity of implementing comprehensive approaches to enhance the efficacy of EMI in other academic fields.